Factors Influencing Lecturers’ Adoption and Use of an Open Source Learning Management System In Universities In Ghana - Asamoah, M.K. (University Of Ghana, 2017)
The deployment of ICT as a teaching and learning tool has long been acclaimed as a catalyst for educational transformation. As a result, universities have invested and continue to invest in e-learning infrastructure including Learning Management Systems (LMS). This thesis identifies the factors influencing lecturers’ adoption and use of an Open Source Learning Management System (LMS) in four universities in Ghana. The overall objective is to analyze factors that influence lecturers’ adoption and use of an Open Source Learning Management System (LMS) in Universities in Ghana in order to enhance e-learning education in the country. The study first, quantitatively examined Innovation Diffusion Theory (IDT), Technology Acceptance Model (TAM), Image, Subjective Norm and Facilitating Conditions variables, and their direct and indirect influence on Actual Use of an Open Source LMS; and second, used a qualitative approach to identify factors that determine lecturers’ adoption and use, and non-use of Open Source LMS. Hypotheses were formulated and tested using Structural Equation Modelling (SEM) to determine whether the predictive generalizations of the theoretical model are valid or not. The study has relevance for e-learning policy formulation and blended learning practice, and adds new knowledge to the existing literature. Theories such as TAM and IDT, related literature on the deployment of ICT in teaching and learning, issues about e-learning education and the use of an Open Source LMS in Ghana were reviewed. Ethical clearance was acquired from the Ethics Committee under the College of Humanities, University of Ghana, Legon. The instrument was piloted with 25 lecturers from University of Ghana and the reliability test results of the pilot study were favourable. For this study, the target population was lecturers of the University of Ghana (Legon); University of Education (Winneba) University of Professional Studies, Accra and Ghana Technology University College, who were aware of, and had been trained for the use of an Open Source LMS such as MOODLE or Sakai. Out of the target population, an accessible population of 435 (consisting of lecturers within the purposefully sampled departments of schools/faculties deemed accessible (by the researcher) in the four Universities) was used for the study. Copies of the modified questionnaire from the pilot study were administered to the accessible population of 435 of which 283 participants fully returned their questionnaire. Homogenous sampling and census were used. Additionally, 20 lecturers were judgmentally sampled and interviewed for the qualitative study and thematic analysis was used to analyse the data. Confirmatory Factor Analysis, Reliability Test and Structural Equation Modelling were used for the analysis of numeric data. Almost all the constructs recorded favourable reliability scores, and convergent, and discriminant validity were also achieved. The study variables were subjected to descriptive analysis for a normality test and an inter-correlation matrix. The mean values, skewness and kurtosis were within the standard. Hypothesized structural relationships among the study variables were tested by conducting SEM with maximum likelihood estimation in IBM AMOS 21.0. The estimated indirect effects were cross-validated using bootstrapping to compute the confidence intervals associated with each indirect effect. Paths that were not significant and those that were significant were discussed in line with other studies. Some key findings were as follows: The fit indices suggested that the 8-factor model showed a good fit to the data: (χ2 = 383.23, df = 271, p < .05; SRMR = .046;TLI = .965; CFI = .971; RMSEA = .038. The SEM results also showed that the hypothesized structural model fitted the data well: (χ2 = 360.39, df = 253, p < .05; SRMR = .048; CFI = .971; TLI = .964; RMSEA = .040. The test of hypotheses showed that Perceived Ease of Use had a positive and significant relationship with Actual Use (β = .45, p < .05). Compatibility had a significantly positive relationship with Perceived Usefulness (β = .62, p < .05) as well as Perceived Ease of Use (β = .43, p < .05).Trialability was found to be positively and significantly related to Perceived Ease of Use (β = .12, p < .05). Subjective Norm was found to be positively related to Perceived Usefulness (β = .17, p < .05). Also, the path from Facilitating Condition to Perceived Ease of Use was positive and significant (β = .36, p = .05). Compatibility and Facilitating Conditions were indirectly and significantly related to Actual Use. Under the qualitative study, Utility of Use, Simplicity of Use, Self-Efficacy, Enablers, Institutional Policy were found to exert influence on Actual Use of Open Source LMS. Factors that determined Non-use of the Open source LMS also included nature of course, restrictive nature of the LMS, difficulty in blending face–to-face teaching with online and slow Internet connectivity. The qualitative study augmented the quantitative results. Implications of the study for future research, e-learning policy, higher education practice, management of lecturers, and methodological additions were highlighted. The limitations of the study included the small sample size (n=20) for the qualitative study and the cross-sectional nature of the quantitative survey. Future studies must include a larger sample size and a longitudinal study for better results. The conclusion was that: the qualitative study corroborated the quantitative study which found out that factors that influence the use of the Open Source Learning Management Systems (LMS) included Simplicity of Use, Utility, Institutional Policy and Enablers. Compatibility and Facilitating Conditions indirectly, positively and significantly influenced Actual Use of Open Source LMS. Perceived Ease of Use had a significant positive relationship with Actual Use. Recommendations made from the study included: regular training and education be organised for faculty (especially laggards and non-users) to appreciate the usefulness of the LMS for possible adoption and use. Universities must make sure that the LMS is made simple to use by ensuring that power, Internet connectivity, appropriate software and technical staff are always available.
Keywords: Open Source Learning; Factors Influencing Lecturers’ Adoption; Use of an Open Source Learning; Open Source Learning Management System In Universities In Ghana